Is motor slowing a universal phenomenon of Aging? Study correlates the effect of aging on psychomotor speed - Kamini Ramdas Ilamkar (Al Ameen Medical College, 2014)
Objectives: The purpose of study was to determine the direct effects of aging on dopamine receptor & prefrontal cortex & their indirect effect on psychomotor speed. Background: Reaction time is mainly a centrally determined function. Its slowing with advancing age is based on various age- induced changes that occur in central nervous system. Damage or dysfunction of basal ganglia may be the basis for psychomotor slowness of speed and reduced D2 dopamine receptor density, a potential biomarkers of aging. After age 20 years, D1 receptors disappear at 3.2% per decade while D2 receptors disappear at about 2.2% per decade. Overall, therefore, the D1/D2 ratio falls with age. Methods: Reaction time is measured by using a response analyzer in healthy controls with age ranging from 20-82 years. Result: It was observed that there is slowness of psychomotor speed with increasing age. Conclusion: Speed of perception, speed of initiating the response and speed of movement are all involved in psychomotor performance. Neural system related to all these functions would be most importantly implicated in the slowing seen as a consequence of aging. It might lead to the delayed or slower reaction time to auditory and visual stimuli in elderly subjects. Damage or dysfunction of basal ganglia may be the basis for psychomotor slowness of speed and reduced D2 dopamine receptor density, a potential biomarkers of aging. Thus motor slowing is a universal feature of human aging commonly expressing human senescence.